2021
DOI: 10.1111/iwj.13737
|View full text |Cite
|
Sign up to set email alerts
|

Uncovering the high prevalence of bacterial burden in surgical site wounds with point‐of‐care fluorescence imaging

Abstract: Detection of bacterial burden within or near surgical wounds is critical to reducing the occurrence of surgical site infection (SSI). A distinct lack of reliable methods to identify postoperative bioburden has forced reliance on clinical signs and symptoms of infection (CSS). As a result, infection management has been reactive, rather than proactive. Fluorescence imaging of bacterial burden (FL) is positioned to potentially flip that paradigm. This post hoc analysis evaluated 58 imaged and biopsied surgical si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
17
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 42 publications
3
17
0
2
Order By: Relevance
“…The current study highlights FL-imaging as an objective solution to address this diagnostic gap by visualising high bacterial loads synchronously across the entire wound/periwound. Consistent with other trials, 24,25,37,[39][40][41] the data herein show a high PPV of FL-imaging and sensitivity well above that of the CSS of infection. Advancing on past works, we also demonstrate that the sensitivity of FL-imaging increases proportionally with bacterial load, while the sensitivity of CSS does not.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The current study highlights FL-imaging as an objective solution to address this diagnostic gap by visualising high bacterial loads synchronously across the entire wound/periwound. Consistent with other trials, 24,25,37,[39][40][41] the data herein show a high PPV of FL-imaging and sensitivity well above that of the CSS of infection. Advancing on past works, we also demonstrate that the sensitivity of FL-imaging increases proportionally with bacterial load, while the sensitivity of CSS does not.…”
Section: Discussionsupporting
confidence: 91%
“…Similarly, Gardner et al 21 reported that the signs and symptoms in the IDSA classification were no better than chance at predicting DFUs with high bacterial loads (defined as >10 6 CFU/g in that study). Other clinical trials have reported similar findings across DFUs, VLUs, pressure injuries, and surgical sites 24,37 . In contrast, delayed wound healing was observed in a large proportion of DFUs in this study, with its frequency increasing as bacterial load thresholds increased from 10 6 to 10 8 CFU/g (41.7%–57.7%).…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…18,19 It is possible to perform swab and biopsy in the most specific point, by identifying the area with pathological fluorescence. 20 Fluorescence Imaging showed higher sensitivity of bacterial detection compared to CSS in a recent case series of 58 surgical site wounds 21 or to the Levine technique in diabetic foot ulcers case series. 22 Moelleken et al reported an average decrease of 29% of bacteria fluorescence after a single mechanical debridement in a case series of 25 venous leg ulcers.…”
Section: Discussionmentioning
confidence: 93%
“…This trial was designed to measure the diagnostic accuracy and utility of this technology in the management of chronic wounds. The primary outcomes of the FLAAG trial demonstrated that the imaging procedure provided accurate, real-time mapping of areas of high bacterial loads greater than 10 4 CFU/g in and around wounds, with a sensitivity 4 to 11-fold greater than CSS alone (standard of care diagnosis) ( Rennie et al., 2017 ; Le L et al., 2021 ; Sandy-Hodgetts K et al., 2021 ). In this study, we are leveraging the information collected during the FLAAG trial from a subset of 78 wounds from which two biopsies were taken.…”
Section: Introductionmentioning
confidence: 99%